FOREIGN VERSUS INDONESIAN AND LOCAL LANGUANGES IN IDENTITY OF BUSINESS ENTITY’S NAME IN SOSROWIJAYAN TOURISM VILLAGE YOGYAKARTA - Hayatul Cholsy (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
The language used in business’ name in the Sosrowijayan tourism village is varied, including the inevitably use of foreign language. This study aims to examine the use of foreign language compared to Indonesian and regional languages in business’ name. The research questions whether the name used shows Javanese and Indonesian identity as a tourism area that represents Yogyakarta. The data is collected through satellite image in Google Maps and in-depth interview with the business’ owner. The names collected are classified according to its form related to the structure and the meaning of business’ name. After that, the data of the business’ name, which relates to its identity, is interpreted using social and cultural approach to understand the strategies used by the meaning of business’ name. The result of this study shows that business’ name as an identity has a purpose to target certain consumers and it is also adjusted to the owners’ identity who are culturally influenced by local, national and international environment.